The Positive Impact of African Drumming on Elderly Participants' Mood and Demeanour. Issue 2 (3rd July 2019) - Roy, Michael; Devroop, Karendra; Bohn, Alicia
Abstract: This article reports on a study that examined the effects of African drumming on the mood and demeanour of older individuals, both those with and those without dementia, in Hong Kong. Previous research indicated that music-making has a positive effect on older adults' overall health and well-being. The study participants' mood and demeanour were measured through observer and self-rating before and after taking part in one of three African drumming sessions. There was a significant improvement in all aspects of all the participants' mood and demeanour after participating in the drumming sessions. A positive impact of the drumming session was also found on the caregivers. The drumming sessions involved physical activity, skill acquisition, reminiscence, joint music making and social interaction that all could have led to the large positive changes in mood and demeanour found in the study participants.